2018
DOI: 10.1111/jcmm.13733
|View full text |Cite
|
Sign up to set email alerts
|

The non‐coding RNA OTUB1‐isoform2 promotes ovarian tumour progression and predicts poor prognosis

Abstract: Ovarian cancer is the leading malignancy of the female reproductive system and is associated with inconspicuous early invasion and metastasis. We have previously reported that the oncogene OTUB1 plays a crucial role in ovarian cancer progression, but the role of its isoform, the non‐coding RNA OTUB1‐isoform2, in ovarian cancer is still elusive. Here, we reported that OTUB1‐isoform2 expression in ovarian cancer tissues was significantly higher than that in the paired paratumorous tissues (P < .01). The patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…In recent years, increasing evidences have shown the oncogenic role of OTUB1, a member of the OTU subfamily of deubiquitinases, in multiple cancers. Previous studies demonstrated that OTUB1 is overexpressed in several carcinomas, including breast cancer, 22 oesophageal cancer 23 and ovarian cancer, 24 but the function of OTUB1 in PTC remains elusive. Here, we demonstrated that OTUB1 was aberrantly overexpressed in PTC specimens and cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, increasing evidences have shown the oncogenic role of OTUB1, a member of the OTU subfamily of deubiquitinases, in multiple cancers. Previous studies demonstrated that OTUB1 is overexpressed in several carcinomas, including breast cancer, 22 oesophageal cancer 23 and ovarian cancer, 24 but the function of OTUB1 in PTC remains elusive. Here, we demonstrated that OTUB1 was aberrantly overexpressed in PTC specimens and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…To explore the underlying function of EYA1 in OTUB1-derived PTC cells proliferation, we carried out rescue experiments and explored OTUB1 is overexpressed in several carcinomas, including breast cancer, 22 oesophageal cancer 23 and ovarian cancer, 24 but the function of OTUB1 in PTC remains elusive. Here, we demonstrated that OTUB1 was aberrantly overexpressed in PTC specimens and cell lines.…”
Section: Eya1 Is Indispensable For Otub1-mediated Ptc Growthmentioning
confidence: 99%